Attenborites janeae: a new enigmatic organism from the Ediacara Member (Rawnsley Quartzite), South Australia. Issue 6 (17th August 2020) - Droser, M. L.; Evans, S. D.; Dzaugis, P. W.; Hughes, E. B.; Gehling, J. G.
Abstract: Attenborites janeae gen. et sp. nov., is a new enigmatic fossil from the Ediacara Member of the Rawnsley Quartzite, South Australia. Attenborites is a well-defined irregular oval to circular fossil preserved in negative hyporelief ranging in length from 4.5–24 mm. Preserved internal grooves and ridges, variable in number and running parallel to the long axis, typically converge towards one end of the specimen. This taxon is unlike any previously described both in terms of overall morphology and in terms of the irregular nature of the outer and inner morphology. While there are no direct morphological characters that suggest that this organism was pelagic, the nature of preservation suggests that a pelagic lifestyle should at least be considered. However, it is not possible to say whether this animal was likely a ctenophore, cnidarian or a pelagic organism of unknown affinity.